Short Fibre Reinforced Cementitious Composites and Ceramics - Herrmann, Heiko; Schnell, Jürgen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume shines a new light on short fibre reinfoced cementitious composites and particle reinforced ceramics. It offers insight from various disciplines like civil engineering, material sciences and micro-mechanics, and collects 9 experimental, numerical and theoretical studies written by top researchers in composite concrete science. The book presents the outcome of the EUROMECH 582 colloquium "Short Fibre Reinfoced Cementitious Composites and Ceramics" held 20 - 22 March 2017, Tallinn, Estonia. .
Failure behavior and magnetic orientation of fibres in composite Materials -- Tensile Creep and long term reliability of cracked UHPFRC -- Swedish Design Guide for Fibre Concrete Structures -- Non-Destructive Evaluation of the Contribution of Polymer-Fiber Orientation and Distribution Characteristics to Concrete Performance during Fire -- Influence of short polypropylene and carbon fibres of cementitious refractory composites -- Fiber orientation in the bottom layer of a small fiber concrete plate -- Image Data Processing to obtain fibre orientation in fibre-reinforced elements using computed tomography scan -- Crack Patterns of GRFC -- Identification and separation of fiber clusters in reinforced concrete -- Environmental SEM and EDX to examine interface characteristics between the cement-paste and steel fibre -- Bond of reinforcement in steel fibre reinforced lightweight concrete -- Short Polymer Fiber Mechanical Behaviour During Pulling out of a Concrete -- Short Composite Fiber for Concrete Disperse Reinforcement -- Highly Workable Steel-Fiber-Reinforced Concrete (SFRC) -- Non-Destructive Evaluation of the Contribution of Polymer-Fiber Orientation and Distribution Characteristics to Concrete Performance during Fire.
Keywords: Building materials; Ceramic materials; Mechanics, Applied; Solids; Structural Materials; Building Materials; Ceramics; Solid Mechanics